Embedding Ethno-Parenting into 21st Century Education Policy: A Technology-Driven Approach to Cultural Sustainability - Mahardhani, Ardhana Januar; Sulton, Sulton; Katoningsih, Sri; Muttaqin, Muhammad Azam; Pramudiana, Ika Devy; Dhika, Gregorius Aquino (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to analyze how cultural identity is reproduced through ethno-parenting, education, and cultural policy in contemporary Indonesia with a specific focus on how digital tools and technology-enhanced learning environments supports this procces. Methodology: This research employs a qualitative ethnographic approach using participant observation, in depth interviews, and document analysis in family settings, schools, art studios, and government agencies. Digital content bservation, including online cultural archives, social media materials, and technology-supported learning platforms, was also incorporated to examine technology-driven cultural transmission. Main Findings: Ethno-parenting serves as the primary mechanism for intilling cultural values through storytelling, rutuals, and performance practices. Formal and non-formal education strenghthens cultural internalization by combining theory and practice. Government policy supports cultural sustainability through festivals, regulations, and training subsides. Technology enhances this ecosystem by enabling digital storytelling, online cultural learning, hybrid participation, and increased youth engagement with cultural content through digital media. Novelty/Originality of this study: This study offers a new perspective by embedding ethno-parenting within 21st century education policy and examining its integration with technology-based learning. It advances existing knowledge by proposing a technology-driven cultural sustainability model that connects family-based cultural transmission, digital learning ecosystems, and contemporary education policy.